KOMPARASI SISTEM PENDIDIKAN DASAR DI INDONESIA, SINGAPURA, DAN JEPANG - Putra Sinambela, Juli; Astria, Mira; Adenti, Julia; Riau Mita, Mutia; Lubis, Hasrita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and compare the basic education systems in Indonesia, Singapore, and Japan based on educational philosophy, curriculum structure, teaching methods, assessment systems, and the role of teachers in learning. The study was motivated by differences in educational quality and student achievement among countries as reflected in various international assessments. The research employed a comparative literature study method. Data were collected from scientific journals, books, research reports, and educational policy documents related to basic education systems in the three countries. The data were analyzed qualitatively through data reduction, categorization, and interpretation. The findings indicate that Singapore emphasizes academic excellence and 21st-century skills, Japan focuses on character building, discipline, and social responsibility, while Indonesia develops the Merdeka Belajar approach which is more flexible and student-centered. The study concludes that the quality of basic education is influenced by policy consistency, teacher competence, learning culture, and support for educational technology.